Analysis of Consumer Buying Interest in Doing Shopee Online Purchase (Case Study on STIE Student Eka Prasetya Medan) - Pesta Gultom (LPPM STIE EKA PRASETYA, 2021)
The purpose of this study was to determine the effect of security, and consumer trust on online shopee shopee buying interest in STIE Eka Prasetya students partially and simultaneously. The population used in this study were all STIE Eka Prasetya students who registered for T.A 2020/2021 who had shopped online shopee, totaling 120 people. Data was collected by distributing online questionnaires via google form with a total sample of 92 respondents. Analysis of the data used is statistical analysis in the form of multiple linear regression test. The results of this study indicate that partially and simultaneously the security variables, and consumer trust have an effect on the online shopee, shopee buying interest in STIE Eka Prasetya students. This is evidenced by the results of the simultaneous test (F test) and the results of the partial test (t-test), which also show significant values of the two independent variables that support the hypothesis. Therefore, the test results from this study state that there is a simultaneous influence between the security variables, and consumer confidence on the online shopee shopee buying interest in STIE Eka Prasetya students, and the effect is 71.7%, this is evidenced by the determination test. So it is suggested to the online shopee shopee management to maintain consumer data and information, so that consumer confidence in buying shopee online shopee increases.